(s, S) policy model for liner shipping refueling and sailing speed optimization problem. (April 2015) - Sheng, Xiaoming; Chew, Ek Peng; Lee, Loo Hay
Highlights: Implemented a ( s, S ) policy to solve a liner shipping operation level problem. Both bunker prices and consumption uncertainties were considered. Proposed two variations of the progressive hedging algorithm to solve our problem. Performed extensive numerical experiments. Abstract: This work expounds on implementing an effective dynamic ( s, S ) policy to solve a liner shipping refueling and speed determination problem under both bunker prices and consumption uncertainties. While solving an optimization model which incorporates a continuous distribution is extremely challenging, we use sample average approximation method to solve it. However, the resulting problem is still a very large-scaled problem. Therefore, we propose two variations of the progressive hedging algorithm to tackle it. Numerical results show that our solution method is efficient and, in addition, our dynamic ( s, S ) policy model has significant cost reduction potential compared to stationary models.